2005
DOI: 10.2460/javma.2005.226.2020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ameroid ring constrictors for treatment for single extrahepatic portosystemic shunts in dogs: 168 cases (1995–2001)

Abstract: Use of an ARC for treatment for a single extrahepatic PSS resulted in low morbidity and mortality rates. Certain preoperative factors were associated with increased risk of postoperative death, continued portosystemic shunting, and long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
279
3
29

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(338 citation statements)
references
References 30 publications
21
279
3
29
Order By: Relevance
“…This finding is similar to reported results of ameroid constrictor placement. [2][3][4][7][8][9]11,12,22 It is possible that in some animals continued biochemical evidence of hepatic dysfunction resulted from persistent flow through the original shunt (as we documented in 1 cat). In other animals, it is likely that persistent shunting results from development of multiple acquired shunts, however, this was confirmed in only two animals.…”
Section: Discussionmentioning
confidence: 93%
“…This finding is similar to reported results of ameroid constrictor placement. [2][3][4][7][8][9]11,12,22 It is possible that in some animals continued biochemical evidence of hepatic dysfunction resulted from persistent flow through the original shunt (as we documented in 1 cat). In other animals, it is likely that persistent shunting results from development of multiple acquired shunts, however, this was confirmed in only two animals.…”
Section: Discussionmentioning
confidence: 93%
“…11,19 In addition, in two recent studies applying AC to single extrahepatic PSS in dogs and cats, 17% of the animals (17% 19 , 17.5% 21 ) were found to have developed multiple extrahepatic shunts at long term follow-up. 19,21 Another study of clinical results after AC in 24 cats with single extrahepatic PSS reported that 8 of 14 cats (57%) had persistent shunting 8-10 weeks after surgery. 22 Use of the AC in combination with a portocaval venograft and complete ligation of single intrahepatic PSS was associated with an even higher rate of continued shunting, with multiple extrahepatic shunts being identified in 4 of 8 dogs at long term follow-up.…”
mentioning
confidence: 98%
“…Whilst the sample size in this study is small, it does suggest that the cats with prolonged PT and aPTT tests prior to surgery are not at increased risk of developing a clinical perioperative bleeding complication. There are reports of dogs with CPSS suffering serious or fatal postoperative haemorrhage, [13][14][15]30 but overt bleeding is overall an uncommon complication in animals with a CPSS, severe liver disease or failure. 1,3,5,8,31 One possible theory for why many of these animals do not become hypocoagulable is that the pro-coagulant system is not affected in isolation.…”
Section: Discussionmentioning
confidence: 99%